Synthesis of Bioactive Organic Compounds Using Green and Environmentally Friendly Catalysts - Gamal Aboulgasem; Al Khansa Saeid; Eman Alsaeh; Antisar Bashouk; Hafed Elgandoz (Journal of Libyan Academy Bani Walid, 2026)
This research investigates the synthesis of bioactive organic compounds through the application of green and environmentally friendly catalysts, addressing the growing need for sustainable alternatives to conventional synthetic methods. The study encompasses a comprehensive framework for developing catalytic routes that minimize environmental impact while maintaining or improving synthetic efficiency. Biocatalysts including enzymes and whole-cell systems, metal-free organocatalysts, heterogeneous recyclable catalysts, and nanocatalysts derived from renewable sources are evaluated in terms of their ability to facilitate the synthesis of pharmacologically relevant compounds including heterocycles, alkaloids, chalcones, and coumarin-fused scaffolds. Reaction conditions are optimized with respect to catalyst loading, solvent selection emphasizing green media such as deep eutectic solvents, water, and Cyrene, temperature, and reaction time. Green chemistry metrics including atom economy, E-factor, reaction mass efficiency, turnover number (TON), and turnover frequency (TOF) are employed to quantitatively assess the environmental sustainability of the developed protocols. Results demonstrate that green catalytic systems achieve yields and selectivities comparable to or exceeding those of conventional methods, while significantly reducing waste generation and toxicity. Recyclable heterogeneous catalysts, including chitosan-based magnetic nanocomposites, biogenic metal nanocatalysts, and ash-derived reagents, demonstrate robust reusability over multiple reaction cycles. The findings underscore the viability of integrating green chemistry principles into the synthesis of biologically active molecules at both laboratory and potentially industrial scales and point toward continuous flow chemistry integration and novel biocatalyst development as the most promising avenues for future progress.